The Impact of Internet Addiction on Mental Health: Exploring the Mediating Effects of Positive Psychological Capital in University Students - Girum Tareke Zewude; Derib Gosim Bereded; Endris Abera; Goche Tegegne; Solomon Goraw; Tesfaye Segon (MDPI AG, 2024)
Introduction: The widespread use of the internet has brought numerous benefits, but it has also raised concerns about its potential negative impact on mental health, particularly among university students. This study aims to investigate the relationship between internet addiction (IA) and mental health (MH) in university students, as well as explore the mediating effects of positive psychological capital (PsyCap) in this relationship. Objective: The main goal of this study was to examine the psychometric properties of the measures and to determine whether internet addiction could negatively predict university students' mental health, mediated through PsyCap. Method: A cross-sectional design with an inferential approach was employed to address this objective. The data were collected using the Psychological Capital Questionnaire (PCQ-24), Internet Addiction Scale (IAS), and Keyes' Mental Health Continuum-Short Form (MHC-SF). The total sample of this study comprised 850 students from two large public higher education institutions in Ethiopia, of whom 334 (39.3%) were female and 516 (60.7%) were male, with a mean age of 22.32 (SD = 4.04). Several analyses were performed to achieve the stated objectives, such as Cronbach's alpha and composite reliabilities, bivariate correlation, discriminant validity, common method biases, and structural equation modeling (confirmatory factor analysis, path analysis, and mediation analysis). Confirmatory factor analysis was conducted to test the construct validity of IAS, PCQ-24, and MHC-SF. Additionally, the mediating model was examined using structural equation modeling with the corrected biased bootstrap method. Results: The preliminary study results found that the construct validity of IAS, PCQ-24, and MHC-SF was excellent and appropriate. Furthermore, the findings demonstrate that internet addiction had a negative and direct effect on PsyCap and MH. Moreover, PsyCap fully mediated the relationship between IA and MH. Additionally, this study confirmed that all the scales exhibited strong internal consistency and good psychometric properties. Conclusion: This study contributes to a better understanding of the complex interplay between IA, PsyCap, and MH among university students, confirming previous findings. Recommendation: The findings, discussed in relation to the recent and relevant literature, will be valuable for practitioners and researchers aiming to improve mental health and reduce internet addiction by utilizing positive psychological resources as protective factors for university students.